24 Patterns of recurrence in vulvar cancer: a nationwide population-based study. (13th November 2020) - Zach, D; Åvall Lundqvist, E; Åvall Lundqvist, H; Hemming, J; Hellman, K; Flöter Rådestad, A
Abstract : Objectives: To explore patterns of recurrence and prognostic factors in patients with vulvar squamous cell carcinoma (VSCC) in Sweden. Methods: A nationwide population-based retrospective cohort study, including women diagnosed with VSCC between 2012–2015 and registered in the Swedish Quality Registry for Gynecologic Cancer. Further information about recurrences and follow-up was retrieved from medical charts. Prognostic factors (groin surgery; age (> 79 years vs < 65 years), stage (I-II vs III-IV)) for recurrence-free (RFS) and overall survival (OS) were analyzed by multivariate regression models. Results: 489 eligible women were included. Median follow-up was 5.3 years. The overall recurrence rate was 22.3%; in 56% local, in 27.5% groin and in 7.3% distant recurrences. 63.3% of all women with a recurrence reported symptoms. Groin surgery was withheld in 13% of women with presumed stage IB-II. Poorer RFS and OS was significantly associated with older age (HR 3.44; p<0.001 for RFS; HR 5.03; p<0.001 for OS), withheld groin surgery (withheld versus performed: HR 0.53; p=0.001 for RFS; HR 0.49; p=0.001 for OS) and advanced FIGO stage (HR 2.41; p<0.001 for RFS; HR 2.48; p<0.001 for OS). Recurrences diagnosed in-between follow-up visitations were significantly larger (30 mm versus 18 mm, p=0.003) but after adjustment for age, type of recurrence and time since treatment not associated with worse survival. Conclusions: This population-based study confirms previous findings of predominantly local recurrences in vulvar cancer. Besides known prognostic factors as age and FIGO-stage, withheld groin surgery was associated with worse RFS and OS. The value of regular follow-up remains undetermined.